2018
DOI: 10.1007/s11307-018-1175-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Remote Myocardium Heterogeneity in Patients with Ventricular Tachycardia Using Texture Analysis of Late Iodine Enhancement (LIE) Cardiac Computed Tomography (cCT) Images

Abstract: PurposeDiffuse remodeling of myocardial extra-cellular matrix is largely responsible for left ventricle (LV) dysfunction and arrhythmias. Our hypothesis is that the texture analysis of late iodine enhancement (LIE) cardiac computed tomography (cCT) images may improve characterization of the diffuse extra-cellular matrix changes. Our aim was to extract volumetric extracellular volume (ECV) and LIE texture features of non-scarred (remote) myocardium from cCT of patients with recurrent ventricular tachycardia (rV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Our results confirmed the feasibility and effectiveness of tissue characterization at CT using LCE (15,16) and ECV (17,18), with good agreement with cardiac MRI (15,31). LCE CT demonstrated a known tendency to underestimate the extension of scar due to the limited LCE CNR compared with that of LGE MRI, in agreement with previous studies (15).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results confirmed the feasibility and effectiveness of tissue characterization at CT using LCE (15,16) and ECV (17,18), with good agreement with cardiac MRI (15,31). LCE CT demonstrated a known tendency to underestimate the extension of scar due to the limited LCE CNR compared with that of LGE MRI, in agreement with previous studies (15).…”
Section: Discussionsupporting
confidence: 90%
“…In the past years, technologic development has positively impacted cardiac CT capabilities from a pure angiographic tool to a complete diagnostic modality able to detect wall motion abnormalities (14) and characterize the myocardium, identifying myocardial scars or necrosis (15,16) and quantifying the myocardial extracellular volume fraction (ECV) (17,18). All these features are considered the cornerstones of differential diagnosis among acute infarction, myocarditis, takotsubo cardiomyopathy, and other causes of acute myocardial injury according to the cardiac MRI literature (19).…”
Section: Ct Protocolmentioning
confidence: 99%
“…They enrolled 161 patients and used logistic regression to create a classification model which proved to have high diagnostic power (AUC = 0.81 in the training set and 0.78 in the testing cohort). Esposito et al used TA to detect extracellular matrix changes in the myocardium of patients with ventricular tachycardia, analyzing late iodine enhancement images and identifying different phenotypes of remodeling [48]. Similarly, the analysis of late iodine enhancement with ML may also be useful in distinguishing cardiac sarcoidosis from non-ischemic cardiomyopathies [49].…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%
“…5 Radiomic texture analysis of late iodine enhancement on CT images reflects left ventricle remodeling and systolic-diastolic function, and may help to identify different patterns of structure remodeling. 6 Coronary plaques are small and have a limited number of voxels, and are therefore very challenging for image analysis. Kolossvary et al demonstrated that the voxels of a coronary plaque were sufficient to perform a radiomic analysis, and found that 21% of radiomic parameters were significantly different between plaques with and without the napkin-ring sign and that radiomic parameters had a higher area under curve (AUC) than conventional parameters (0.92 vs 0.75).…”
Section: Technical Aspects Radiomicsmentioning
confidence: 99%